Performance of local coconut (Cocos nucifera L.) germplasm under Assam conditions of the North East region of India - Singh, L S; Niral, V; Acharya, G C; Chaithra, M; Alpana, Das; Jyoti, Roy (Plant Science Today, 2026)
The study was carried out to elucidate the performance of local coconut accessions collected from different parts of Assam in the North East region of India, an experiment was conducted at the Research Centre, ICAR-Central Plantation Crops Research Institute. Observations were recorded on growth, yield, fruit and nut characters and tender nut water and quality of 13 local coconut accessions. The experiment was laid out in 3 replications, with 4 palms per replication. The study showed that accession, KKHC 4 produced the highest nut yield and kernel content, indicating its potential suitability for cultivation in the North East region. Accession KKHC 6 exhibited enhanced fruit size and a higher volume and quality of tender nut water, suggesting its value for both fresh consumption and beverage markets. These findings highlight the necessity for region specific coconut improvement programs and underscore the importance of selecting and promoting locally adapted germplasm.